Exploring Hybrid Third Spaces in the Place Mappings of Malawian Youth - Jean Kayira (Environmental Association of Southern Africa, 2018)
This article is based on a study of Malawian youths' understandings of place in relation to knowledge and practice and considers some implications for education. The study was conducted at Chinduzi Junior Farmer Field and Life Skills School in Machinga district in Malawi from September 2010 through January 2011. Data collection methods included place mapping and associated focus group discussions. The data were analysed following Collier and Collier's (1986) method for analysing photographs. Youth mappings of their favourite places suggested aspects of both hope and despair. From the youths' discussions, a sense of belonging was evident in the social relationships associated with the activities performed in their favourite places. The drawings also exhibited gendered features. Overall, the drawings and associated discussions revealed that the youth are largely rooted in their socio-cultural interactions within their community, but also influenced by globalisation - hence they operate within what Homi Bhabha (1994) calls 'hybrid third spaces'. In these spaces, they use their imagination to create optimistic futures. These findings have implications for environment-related education. People are part of and shaped by place; at the same time, they shape place through everyday social practices. Thus, studies on environment-related education in a particular local context need to take into account variations in experience based on learners' diverse backgrounds. Pedagogical engagements should consider the socio-cultural experiences of learners in particular contexts.